Resistance in pea (Pisum sativum var arvense) genotypes to leaf miner (chromatomyia horticola) - MEHTA, P K; SHARMA, T N; CHANDEL, R S (The Indian Journal of Agricultural Sciences, 2013)
A study was conducter during 1993-94 and 1994-95 to evaluate 40 genotypes of pea ( pisum sativum L. var arvense Poir.) for resistance to leaf miner (Chromatomyia horticola Goureau) at Palampur. None genotypes was immune to the pest.On the basis of infestation index values (calculated by combining relative leaflet infestation and number of maggots/ plant) only 6 genotypes, viz 'NDVP 1','KS 136','KS 226','VG 5','KS 225' and FC 1', were categorized as resistant ( 1.40 infesttation index) were rated as highly susceptible.